Higher Degree by Research Factors for Indigenous Student Success - Anderson, Peter; Blue, Levon; Pham, Thu; Saward, Melanie (SpringerBriefs in Education,, 2022)
This open access book provides insights from Indigenous higher degree research (HDR) students on supervision practices in an Australian context. It examines findings from qualitative studies conducted with Indigenous HDR students from different academic disciplines, enrolled higher education institutions across Australia, and supervisors of Indigenous HDR students. Six types of data and their thematic analyses are presented, to understand the needs and experiences of both Indigenous HDR students and supervisors of Indigenous HDR students. This book also unpacks assumptions and commonly held beliefs about Indigenous HDR students, and shares what Indigenous HDRs report they need to experience success in higher education. It reports the experiences of supervisors of Indigenous HDR students, and explore further opportunities which enhance the higher education experiences of Indigenous HDR students. This book also suggests how successful relationships between Indigenous HDR students, and their supervisors may be fostered, and aims to be a useful resource for Indigenous peoples wishing to pursue higher education, and HDR supervisors in countries with Indigenous populations.